The Nutritional Status of Athletes in the Athletics Branches of DKI Jakarta During the Covid-19 Period Based on Anthropometry - Khurotul Aini; Aisya Kemala (STKIP Muhammadiyah Kuningan, 2021)
Changes in the habit of consuming food at regular training venues to the homes of individual athletes during a pandemic should still meet the nutritional needs of the athletes. The performance of athletes in athletic sports must be supported by good nutrition, even during the Covid-19 period. This research uses descriptive quantitative research techniques with survey methods using google form with data analysis using percentages. The purpose of this study was to determine the level of assessment of the nutritional status of athletes in athletic in DKI Jakarta. Based on the research conducted, it revealed that as many as 100% (n = 104) of the research subjects were athletic athletes under the auspices of the DKI-Jakarta Government, 44 were female and 66 were male. Anthropometry results for male athletes showed an average nutritional status at BMI of 32.89 with over nutritional status and for female athletes at BMI of 32.68 with over nutritional status. Hence, the average nutritional status of athletes in athletic sports in DKI Jakarta is in the category of excess nutrition in the Covid-19 condition. Based on the anthropometric assessment of athletes in athletic sports during the Covid-19 period, excess nutritional status was obtained.